Decision-making process in shipping finance: A stochastic approach - Marina Maniati; Evangelos Sambracos (Cogent Economics & Finance, 2017)
Shipping markets irregularity due to high-level volatility of freight rates and asset prices increases the risk of banks' invalid financial strategy. Risk is further increased due to the heterogeneous shipping market, despite the regulations set by the Basel Convention. Consistent with the above, the present work contributes to the existing methodological aspects of bank's financial strategy on shipping finance by enhancing the role of the credibility theory, which balances the individual bank policy with the market as a whole. This has been primarily forwarded on by the analysis of the operational environment's internal factors of an individual bank combined with the whole shipping banks' loans portfolio by estimating the credibility factor to the decision of the bank to either increase or decrease financing in the relevant market. The important factors extracted from the principal components analysis are linked with interest income on loan and operating profit accounts. The final model predicts that the optimal decision is positive driven by both the aforementioned dependent variables, while the interest income on loan variable has more influence compared with that of the operating profit variable. In the absence of the influence of the dependent variables, the bank's decision strategy matches the market's strategy by 77% that decreases as the dependent variables increase their influence.
Keywords: G21; G31; P33; 330; credibility factor; shipping finance; bank loan decision; Bühlmann